PENGEMBANGAN MEDIA POCKET BOOK DIGITAL BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN PPKN TEMA 7 KELAS IV SD - Widiastuti, Tri; Hidayat, Otib Satibi; Adnan, Evita (Universitas Negeri Surabaya, 2024)
This research and development aims to produce a media product in the form of a PBL-based digital pocket book for Civics learning Theme 7 The Beauty of Diversity in My Country in grade IV of elementary school. This study uses the ADDIE development method which has five stages, namely Analysis, Design, Development, Implementation and Evaluation. Product validation trials in this study involved three experts, namely material experts, linguists and media experts. In addition to these three experts, this development involved fourth grade students and teachers at SDIT Cendekia Islamic School Bekasi in product validation trials. The collection of information in this study was obtained based on the results of observations and interviews with teachers and fourth grade students and questionnaires. The validation results of material experts were 77.8%, linguists 85.4%, and media experts 88.75%. So as to obtain the overall results of expert test validation with an average of 83.98%. The results of product trials on One To One were 81.3%, Small Groups were 86%, and Field Tests were 91.3%, as well as teacher validation results were 91%. Thus, this shows that PBL-based digital pocket book media is feasible to be used as an additional learning media for fourth grade elementary school students.